2011
DOI: 10.3109/10715762.2011.555481
|View full text |Cite
|
Sign up to set email alerts
|

8-Hydroxyguanine levels and repair capacity during mouse embryonic stem cell differentiation

Abstract: To evaluate the defence capacities of embryonic stem (ES) cells against gene impairment, this study measured the levels of 8-hydroxyguanine (8-OH-Gua), a well-known marker of oxidative stress in DNA, and its repair capacity during differentiation. Undifferentiated ES cells (EB3) were cultured without leukaemia inhibitory factor (LIF) for 0, 4 and 7 days and are referred to as ES-D0, ES-D4 and ES-D7, respectively. These three cell lines were treated with 300 μM hydrogen peroxide (H(2)O(2)) for 48 and 72 h. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A comparison of embryonic stem cells to more differentiated cells did not reveal any impact on the mRNA levels of MUTYH, in contrast to OGG1, which decreased upon differentiation (Kuboyama et al, 2011). Alimentary supplementation with quercetin, a plant-derived flavonoid that has been attributed with anticarcinogen, was found to enhance the expression of MUTYH in the distal colon mucosa of rats (Dihal et al, 2008).…”
Section: Regulation Of Mutyhmentioning
confidence: 99%
“…A comparison of embryonic stem cells to more differentiated cells did not reveal any impact on the mRNA levels of MUTYH, in contrast to OGG1, which decreased upon differentiation (Kuboyama et al, 2011). Alimentary supplementation with quercetin, a plant-derived flavonoid that has been attributed with anticarcinogen, was found to enhance the expression of MUTYH in the distal colon mucosa of rats (Dihal et al, 2008).…”
Section: Regulation Of Mutyhmentioning
confidence: 99%
“…Our findings are consistent with previous studies which showed that ROS play crucial roles as secondary messengers during stem cell differentiation into various somatic lineages [10,11], so that an increase in ROS levels in differentiated stem cell progenies is therefore expected. Hirano and Tamae [12] and Kuboyama et al [13], also reported that undifferentiated embryonic stem cells were more resistant to DNA damage induced by the ROS -8-oxoguanine (which is known to generate GC-to-TA point mutations in genomic DNA), as compared to their differentiated progenies. These findings are thus consistent with the results of this study, as well as our previous studies [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that the defense capacity against 8-oxo-Gua was also higher in ES cells than in their differentiated counterparts [12]. In the study, we measured the 8-oxo-Gua generation level in the DNA of ES cells and their differentiated counterparts.…”
Section: Differentiation Of Es Cells and Dna Damage / Dna Repair Systemsmentioning
confidence: 97%
“…Our study provided valuable information for the use of stem cells for regenerative medicine in the future. In this short review, we describe oxidative DNA damage and ES cell differentiation, by summarizing our previous work [12] and that of other researchers.…”
Section: A) B)mentioning
confidence: 99%